Formulation And Physical Quality Test Of Lip Balm Rosella Flower Extract (Hibiscus Sabdariffa L.) As A Lip Moisturizer And Natural Color - Lailiyah, Munifatul; Sony Andika Saputra; Erfan Tri Prasongko; Ida Kristianingsih (Sean Institute, 2024)
Background: Lip balm, also known as lip balm, functions to moisturize the lips so they don't get dry and chapped by sunlight, pollution, temperature, and weather. One natural ingredient that functions as a lip moisturizer is the rosella flower (Hibiscus sabdariffa L.), which has many cosmetic benefits such as vitamin C, antioxidants, and anthocyanins, which can moisturize the lips and give them a natural color. Objective: This research is to determine how the concentration of rosella flower extract (Hibiscus sabdariffa L.) impacts the physical quality test and moisture test of rosella flower extract lip balm preparations with concentrations of 0%, 6%, 8%, and 10%. Results: Physical quality tests showed that the formulation was stable. The results of organoleptic, homogeneity, pH, irritation, stability, and moisture tests did not show significant differences in varying extract concentrations. In the moisture test, the percentage of moisture test for formulation 0 was 15.5%, formulation I was 22.4%, formulation II was 28.7%, and formulation III was 35.4%. Conclusion: The results of the physical quality test were not influenced by differences in the concentration of rosella flowers in each formulation. Formulation III has a concentration of 35.4%, which is the most moist.